2023
DOI: 10.3389/fcimb.2022.1077494
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoid-mediated horizontal transmission of Rickettsia between whiteflies

Abstract: Intracellular bacterial endosymbionts of arthropods are mainly transmitted vertically from mother to offspring, but phylogenetically distant insect hosts often harbor identical endosymbionts, indicating that horizontal transmission from one species to another occurs in nature. Here, we investigated the parasitoid Encarsia formosa-mediated horizontal transmission of the endosymbiont Rickettsia between different populations of whitefly Bemisia tabaci MEAM1. Rickettsia was successfully transmitted from the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…and C. sinica in the current study were clustered into one branch of Con subgroup in the supergroup B, which can assist in predicting the roles of Wolbachia in D. citri and C. sinica. Wolbachia can also be horizontally transmitted between intraspecies of insect hosts (Ahmed et al, 2013;Chu et al, 2016;Li Y. H et al, 2017;Liu et al, 2023). For example, by comparing the phylogeny of different Bemisia species and their endophytes, Ahmed et al (2013) revealed the discordance of Wolbachia with their whitefly hosts and testified that Wolbachia can achieve host transfer through horizontal transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and C. sinica in the current study were clustered into one branch of Con subgroup in the supergroup B, which can assist in predicting the roles of Wolbachia in D. citri and C. sinica. Wolbachia can also be horizontally transmitted between intraspecies of insect hosts (Ahmed et al, 2013;Chu et al, 2016;Li Y. H et al, 2017;Liu et al, 2023). For example, by comparing the phylogeny of different Bemisia species and their endophytes, Ahmed et al (2013) revealed the discordance of Wolbachia with their whitefly hosts and testified that Wolbachia can achieve host transfer through horizontal transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Wolbachia can also be horizontally transmitted between intraspecies of insect hosts ( Ahmed et al., 2013 ; Chu et al., 2016 ; Li S. J et al., 2017 ; Li Y. H et al., 2017 ; Liu et al., 2023 ). For example, by comparing the phylogeny of different Bemisia species and their endophytes, Ahmed et al.…”
Section: Discussionmentioning
confidence: 99%